2006
DOI: 10.1016/s0022-5347(06)00489-7
|View full text |Cite
|
Sign up to set email alerts
|

Access Related Complications During Percutaneous Nephrolithotomy: Urology Versus Radiology at a Single Academic Institution

Abstract: Despite similar access difficulty between groups, access related complications were less and stone-free rates were improved during urologist acquired percutaneous access. Urologists instructed in percutaneous access may be able to provide improved stone-free rates during percutaneous nephrolithotomy while minimizing access related complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
68
0
5

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(74 citation statements)
references
References 10 publications
1
68
0
5
Order By: Relevance
“…When PCA is performed by the urologist rather than the interventional radiologist, PCNL outcomes are better [13]. In addition, competency in PCA allows urologists to be independent from interventional radiologists in terms of the time and place of obtaining the PCA.…”
Section: Discussionmentioning
confidence: 99%
“…When PCA is performed by the urologist rather than the interventional radiologist, PCNL outcomes are better [13]. In addition, competency in PCA allows urologists to be independent from interventional radiologists in terms of the time and place of obtaining the PCA.…”
Section: Discussionmentioning
confidence: 99%
“…PC access performed by a radiologist is a practical option, often employed. However, PC access related complications are fewer and stone-free rates are higher with urologist-acquired access (3,13).…”
Section: Commentsmentioning
confidence: 99%
“…1 Furthermore, in a retrospective single centre study comparing complications of urologist-directed versus interventional radiologist-directed PCA for patients undergoing PCNL, there were significantly lower complications and higher stone-free rates whenever the PCA was performed by the urologist. 2 However, the learning curve of PCNL is quite long. It is reported that 36 to 45 cases are needed to achieve competency and 105 to 115 cases to achieve proficiency.…”
Section: Introductionmentioning
confidence: 99%